Logo impact on consumer’s perception, attitude, brand image and purchase intention: a 5 years systematic review - Liang, Lyu; Zainal Abidin, Sazrinee; Shaari, Nazlina; Yahaya, Mohd Faiz; Jing, Lyu (Human Resources Management Academic Research Society (HRMARS), 2024)
The logo is the most crucial element in corporate visual identity design, and there is a growing of research and review literature on this subject. However, comprehensive literature reviews on the holistic impact of logos were not update until 2019, lacking the latest advanced knowledge. Therefore, this paper further refresh the research progress on logo in the last five years, providing a comprehensive understanding of the latest studies on how logo influence consumer perceptions, cognitions and behaviors. The paper collected 331 articles from the years 2019 to 2023 in the two databases, Web of Science and Scopus, selected 50 core articles for an in-depth thematic review and synthesis. The findings reveal that the impact of logo on consumers can be categorized into six major classes: brand awareness, brand perception, brand attitude, brand image, purchase intention, and customer loyalty, forming a systematic framework from cognition to behavior. Finally, the paper suggests that future research should supplement more effects generated by logo and explore the logical relationships between impacts, the sequence in which impacts occur, and comprehensive studies of their effects. Providing business managers and designers with more recommendations for logo design, triggering consumer purchase intention, and enhancing corporate performance.